ANALISIS PENGARUH TATA KELOLA CORPORATE SOSIAL RESPONSIBILITY DAN KINERJA CORPORATE SOSIAL RESPONSIBILITY BERORIENTASI LINGKUNGAN DAN SOSIAL TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Benanda, Even; Parasetya, Mutiara Tresna (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of corporate social responsibility (CSR) governance and environmental and social-oriented corporate social responsibility (CSR) performance on corporate financial performance. The independent variables in this study are CSR governance, CSR performance that is environmentally and socially oriented. Meanwhile, the company's financial performance is the dependent variable whose measurement uses Tobin's Q. This research refers to research conducted by (Wang & Sarkis, 2017).The characteristics of CSR governance and environmental and social oriented CSR performance are considered to have a positive influence on the level of corporate financial performance in accordance with the hypothesis based on the theory of legitimacy and stakeholder theory. The population in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) during 2017-2019. The sampling method used in this study was purposive sampling method with predetermined criteria resulting in 121 samples of non-financial companies to be studied. The data used are secondary data in the form of financial reports and company annual reports obtained through the website www.idx.co.id and financial information from the Bloomberg terminal. This study uses multiple linear regression analysis, classic assumption test consisting of normality test, autocorrelation test, multicollinearity test and heteroscedasticity test as well as hypothesis testing, namely the F statistical test, t statistical test, and the coefficient of determination.The results of the statistical test in this study indicate that environmental-oriented CSR performance has a positive effect on the company's financial performance (Tobin's Q). Meanwhile, social-oriented CSR performance has a significant negative effect on financial performance (Tobin's Q). However, CSR governance has a positive but insignificant effect on financial performance (Tobin's Q).